The Wall Paintings of Tell el-Dab’a: Potential Aegean Connections - Sara Cole (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2010)
In 1991 Manfred Bietak discovered wall paintings produced in the Aegean style with Aegean techniques at the Egyptian Delta site of Tell el-Dab’a, or ancient Avaris. These paintings date to Egypt’s 18th Dynasty (c.1550-1069 B.C.) and were found in a palatial context. A close examination of the paintings regarding materials and techniques, iconography, style and context sheds new light on the relationship between Egypt and the Aegean world during the 2nd millennium B.C. Additionally, it provides increased support for a system of an elite shared cultural koiné in the eastern Mediterranean during this time, which the elites of each culture appropriated for their own use.
Keywords: Undergraduate Research; Pursuit